The Ethics “Fix”: When Formal Systems Make a Difference - Smith-Crowe, Kristin (Journal of business ethics, 2015)
This paper investigates the effect of the countervailing forces within organizations of formal systems that direct employees toward ethical acts and informal systems that direct employees toward fraudulent behavior. We study the effect of these forces on deception, a key component of fraud. The results provide support for an interactive effect of these formal and informal systems. The effectiveness of formal systems is greater when there is a strong informal “push” to do wrong; conversely, in the absence of a strong push to do wrong, the strength of formal systems has little impact on fraudulent behavior. These results help to explain why the implementation of formal systems within organizations has been met with mixed results and identifies when formal systems designed to promote ethical behavior will be most efficacious.